Natural course of unruptured intracranial aneurysms: a case surveillance study in China - An, Xiuhu; Huan, Linchun; Liu, Pengran; Zhao, Yan; Zhang, Nai; Li, Yaohua; Lin, Yunpeng; Wang, Jiwen; Hao, Jiheng; Yang, Xinyu; Wang, Bangyue (Frontiers in Neurology, 2025)
BackgroundThe natural course of unruptured intracranial aneurysms (UIAs) has been well described in developed countries, but there is a lack of large studies on UIAs in China. This article aims to fill this gap by detailing the current status and natural course of UIAs in China and identifying the major risk factors for their rupture, providing a basis for clinical decision-making.MethodsWe included all patients with UIAs consecutively admitted to 12 tertiary care centers in 4 provinces in northern China between January 2017 and December 2020. The mean follow-up was 3.1 years (range 0–7.3 years). The current status of UIA patients in China was described in detail. Risk ratios for rupture were analyzed using the Cox proportional hazards model, and Kaplan–Meier curves were analyzed for long-term rupture rates.ResultsIn this study, among the 1,475 patients, 33.4% declined surgical treatment. Of the 1,189 patients who completed follow-up, 10.3% initially received conservative treatment but later underwent surgery. A total of 1,337 patients with UIAs who met the criteria were included in the statistical analysis. The annual rupture rate was 1.75%. Cox proportional hazards model identified the following risk factors for rupture: age over 70 years (HR 2.136, 95% CI 1.302–3.504, p = 0.003), aneurysm size of 10–20 mm (HR 3.543, 95% CI 1.501–8.363, p = 0.004) and ≥20 mm (HR 4.455, 95% CI 1.034–19.187, p = 0.045). ICA (HR 0.427, 95% CI 0.203–0.897, p = 0.025) was a protective factor.ConclusionIn China, treatment options for UIA patients are unique, with a low willingness to undergo surgery leading to a higher rupture rate. A significant percentage of Chinese patients refuse treatment, and those who initially choose conservative management are unlikely to opt for surgical intervention later. Advanced age, specific locations, and size are associated with UIA rupture. This study has important implications for clinical decision-making, public awareness of UIAs, and the development of health policies.